2022
DOI: 10.3389/fphar.2022.1036030
|View full text |Cite
|
Sign up to set email alerts
|

From tryptamine to the discovery of efficient multi-target directed ligands against cholinesterase-associated neurodegenerative disorders

Abstract: A novel class of benzyl-free and benzyl-substituted carbamylated tryptamine derivatives (CDTs) was designed and synthesized to serve as effective building blocks for the development of novel multi-target directed ligands (MTDLs) for the treatment of neurological disorders linked to cholinesterase (ChE) activity. The majority of them endowed butyrylcholinesterase (BuChE) with more substantial inhibition potency than acetylcholinesterase (AChE), according to the full study of ChE inhibition. Particularly, hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Melatonin also inhibits the NF-κB pathway in OGD/R or H 2 O 2 -treated SH-SY5Y cells and shows anti-inflammatory and neuroprotective effects. , However, the poor pharmacokinetic properties of melatonin, such as the short plasma half-life (∼30 min), limit its use in neurological disorders; thus, rational modifications based on the template of melatonin have been conducted. Wang et al found that the N -salicyl tryptamine derivative LZWL02003 outperformed all other compounds in terms of its anti-inflammatory, free radical scavenging, and neuroprotective capabilities. , Neuroprotective effects of LZWL02003 were also shown in in vivo and in vitro models of Alzheimer’s disease conferred by Aβ . Therefore, LZWL02003 could also be neuroprotective in the case of cerebral I/R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin also inhibits the NF-κB pathway in OGD/R or H 2 O 2 -treated SH-SY5Y cells and shows anti-inflammatory and neuroprotective effects. , However, the poor pharmacokinetic properties of melatonin, such as the short plasma half-life (∼30 min), limit its use in neurological disorders; thus, rational modifications based on the template of melatonin have been conducted. Wang et al found that the N -salicyl tryptamine derivative LZWL02003 outperformed all other compounds in terms of its anti-inflammatory, free radical scavenging, and neuroprotective capabilities. , Neuroprotective effects of LZWL02003 were also shown in in vivo and in vitro models of Alzheimer’s disease conferred by Aβ . Therefore, LZWL02003 could also be neuroprotective in the case of cerebral I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that the N-salicyl tryptamine derivative LZWL02003 outperformed all other compounds in terms of its anti-inflammatory, free radical scavenging, and neuroprotective capabilities. 10,25 Neuroprotective effects of LZWL02003 were also shown in in vivo and in vitro models of Alzheimer's disease conferred by Aβ. 13 Therefore, LZWL02003 could also be neuroprotective in the case of cerebral I/R.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Neurocognitive disorders encompass a range of conditions that adversely lead to the impairment of cognitive abilities, including memory, executive function, and attention, often due to underlying neurological disorders, damage, or even dementia, where the decline in cognitive function is severe enough to interfere with daily life [1,2]. Among 2 of 30 many others, these disorders include Alzheimer's disease (AD), Parkinson's disease with Dementia (PDD), HIV-associated neurocognitive disorders (HAND), and glioma, each of which presents with distinct causes and clinical manifestations [3,4]. Moreover, the molecular changes resulting from these diseases occur in various brain regions, involving various genes and proteins.…”
Section: Introductionmentioning
confidence: 99%